Penggunaan Media Flash Card Berbasis Kearifan Lokal Terhadap Kemampuan Membaca Siswa Dengan Hambatan Fungsional Belajar - Baiq Sri Hulfa; Donna Boedi Maritasari; Hadiatul Rodiyah (Departement of Mathematics Education, 2023)
This objective of this research to analyze the factor that influence the reading difficulties of students with functional learning disabilities, and to assess the effecacy of employing flash card media based on local wisdom on the reading ability of students with functional learning difficulties. The descriptive qualitative research method was applied, employing a case study methodology. This study’s participants were five third-grade students from SDN 2 Kesik who had functional learning difficulties. Observation, interviews and documentation were utilized to gain data. Data were analyzed using data collection, data reduction, data presentation, and conclusion/verification. The findings indicate that using flash card media based on local wisdom is helpful for sharpening students’ memory as well as improving the reading skills of students with functional learning disabilities at the level of reading, identifying letters and spelling. This can be observed through the students’ improving reading skills indicators.